Model-Based Learning Environment Based on The Concept IPS School-Based Management - Hamid Darmadi (STKIP Singkawang, 2017)
The results showed: (1) learning model IPS-oriented environment can grow and not you love the cultural values of the area as a basis for the development of national culture, (2) community participation, and the role of government in implementing learning model of IPS-based environment provides a positive impact for the improvement of management school resources, (3) learning model IPS-based environment effectively creating a way of life together peacefully, increase the intensity of togetherness and mutual respect (4) learning model IPS-based environment can improve student learning outcomes, (5) there are differences in the expression of attitudes and results learning among students who are located in the area of conflict with students who are outside the area of conflict (6) analysis of the scale of attitudes among school students da SMA result rewards high school students to the values of unity and nation, respect for diversity and peaceful coexistence, It is recommended that the Department of Education authority as an institution of Trustees and the development of social and cultural values in the province can apply IPS learning model based environments.